Ekstraksi Khitosan dari Kepala Udang Putih (Penaeus merguensis) - Yunizal Yunizal; Ninoek Indriati; Murdinah Murdinah; Thamrin Wikanta (agriTECH, 2001)
In order to optimize the utilization of shrimp head, study on extraction of chitosan from head of white shrimp (Panaeud merguensis) was carried out. The aim of the study was to find out the optimum conditions of deproteinization, demineralization and deacetylation process in the extraction of chitosan. The result showed that the most suitable condition of deproteinization process was obained by boiling shrimp head in solution of NaOH 3 % at 100°C for 90 minutes with the ratio of solution and shrimp head 6 : 1 (v/w). However the most suitable condition of demineralization process was obtained by dipping of deproteinized shrimp head in HCl 1,25N solution for 20 hours at ambient temperature. Futhermore, the most suitable condition for deacetylation process was achieved by heating demineralized shrimp head in NaOH 50% solution at 100°C for 90 minutes. As final product, chitosan contained: 6.73% moisture, 6.74% total nitrogen (d.b), 1.00% totla ash (d.b), while the degree of deacetylation and viscosity were 83.10% and 3.50 cps, respectively.